Segmentation of Village Accessibility of Education Service Facilities in Ogan Komering Ulu Selatan Regency - Ahmad Rahmadhan Mustar; Kiagus Muhammad Sobri; Sriati Sriati (Magister Administrasi Publik, 2022)
Education is one of the most important aspects in the development and every citizen has the right to education, and the government is obliged to finance as mandated in the 1945 Constitution. However, the disparity in education access and equity is a problem faced by education in various regions in Indonesia, especially in rural areas. One of the efforts to solve the disparity in educational facilities in rural areas is to carry out village development by increasing the availability and accessibility of educational facilities through the village fund policy. Problem structuring is needed to formulate problems and produce knowledge about what problems must be solved, so that the use of village funds in increasing the accessibility of educational facilities is effective and efficient. In policy analysis, problem formulation is very important, so that the implemented policy resolves the right problems and avoids type III errors. One of the methods used in problem structuring is the classification method. Classification/segmentation of educational facilities accessibility is conducted using the Self Organizing Map algorithm approach. The results of the classification will map the problems and conditions of accessibility of village education facilities in Ogan Komering Ulu Selatan regency into several segments or clusters. This information can be used as a guide for the government in planning or determining development priorities, so that type III errors do not occur, particularly in the development of accessibility of educational facilities in villages. Thus, the use of village funds or other public policies resolves the right problems.